2001
DOI: 10.1002/cem.634
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for screening discrete variations in organic synthesis

Abstract: SUMMARYIn this paper we present a general strategy for screening discrete variations in organic synthesis. The strategy is based upon principal properties, i.e. principal component characterization of the constituents defining the reaction system. The first step is to select subsets of test items from each class of constituents defining the reaction space, i.e. substrates, reagents, solvents, catalysts, etc., so that the selected items from each class cover the properties considered. The second step is to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Principal Properties selection is based on PCA and deflation of the data matrix X by orthogonal projection [8]. The first step is to perform PCA on the data matrix.…”
Section: Principal Properties Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal Properties selection is based on PCA and deflation of the data matrix X by orthogonal projection [8]. The first step is to perform PCA on the data matrix.…”
Section: Principal Properties Selectionmentioning
confidence: 99%
“…Commonly used approaches are Federov's D-optimality algorithm [6] and the Kennard-Stone selection method [7]. An intriguing contribution to this subject was made by Carlson et al [8], who demonstrated how the Principal Properties of a sample can be used as selection criteria for identifying optimal chemical agents in organic synthesis. In this work, we compare these three chemometric subset selection methods with a Cluster-Based approach as commonly used in data-mining [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Subset selection algorithms are also of interest outside calibration transfer ( Allesø et al , 2007 ). The most often used algorithms in the literature are the leverage-based methods, the Kennard-Stone selection ( Kennard and Stone, 1969 ) algorithm and principal properties selection ( Carlson et al , 2001 ). The Kennard-Stone algorithm adds samples that are farthest away from the previously selected set of points.…”
Section: Data Set and Transfer Set Selectionmentioning
confidence: 99%
“…This can be accomplished by selecting new solvents for which the corresponding row in C is most parallel to the singular vector v i that corresponds to the smallest singular value σ i of X . A full account of these aspects is given in ref . By this principle, additional solvents can be selected to improve the precision of the estimated model parameters, and the following next six complementary solvents are: morpholine, pyridine, 1,2-dichloroethane, cis -decaline, 1,2-diaminoethane, and diglyme.…”
Section: Fischer Indole Synthesismentioning
confidence: 99%
“… a The numbers within parentheses refer to the run number in the entire data set (162 runs) given in refs , . b Percent regioisomeric excess. …”
Section: Fischer Indole Synthesismentioning
confidence: 99%